A prospective study of early removal of the urethral catheter after colorectal surgery in patients having epidural analgesia as part of the Enhanced Recovery After Surgery programme. (24th June 2013) - Stubbs, B. M.; Badcock, K. J. M.; Hyams, C.; Rizal, F. E.; Warren, S.; Francis, D.
Abstract Aim Early removal of the urethral catheters is part of the enhanced postoperative recovery programme (ERAS). The effect of epidural anaesthesia on urinary retention was investigated in patients after colorectal resection. Method A prospective cohort study of all patients having colorectal surgery within an ERAS programme that included insertion of an epidural catheter over the last 5 years. Results Two‐hundred and ten patients had an epidural and a urethral catheter postoperatively. The duration of catheterization was not recorded in one patient who was therefore excluded from the study. One‐hundred and eighteen patients had a trial without catheter (TWOC) prior to stopping the epidural (early TWOC). Ninety‐one patients had TWOC after the epidural was stopped (late TWOC). Sixteen (7.6%) patients went into urinary retention (14 early TWOC and two late TWOC). The rate of urinary retention in the early TWOC group was significantly higher than that in the late TWOC group (11.9% vs 2.2%; χ2, P = 0.009). Those who underwent a laparoscopic resection were significantly more likely to have undergone an early TWOC (χ2, P = 0.001); however, there was no difference in retention rates between open and laparoscopic surgery (χ2, P = 0.402). Pelvic surgery was not significantly associated with an increased risk of postoperative urinary retention (χ2, P = 0.627). Male sex was not significantly associated with urinary retention (χ2, P = 0.087). In the early TWOC group 86% had the catheter removed within 24 hours of surgery. Conclusion Early TWOC with epidural analgesia running significantly increases the risk of urinary retention; however, it was still successful in 88% of patients.